2007
DOI: 10.1083/jcb.200605199
|View full text |Cite
|
Sign up to set email alerts
|

A centriole- and RanGTP-independent spindle assembly pathway in meiosis I of vertebrate oocytes

Abstract: Spindle formation is essential for stable inheritance of genetic material. Experiments in various systems indicate that Ran GTPase is crucial for meiotic and mitotic spindle assembly. Such an important role for Ran in chromatin-induced spindle assembly was initially demonstrated in Xenopus laevis egg extracts. However, the requirement of RanGTP in living meiotic cells has not been shown. In this study, we used a fluorescence resonance energy transfer probe to measure RanGTP-regulated release of importin β. A R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
235
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(265 citation statements)
references
References 50 publications
20
235
0
3
Order By: Relevance
“…At MI stage, a similar cortical structure develops as the spindle approaches the cortex. While Ran gradient is indeed generated by chromosomes in MI in mouse oocytes [Dumont et al, 2007b], further investigation is required to test if Ran is involved in cortical polarization.…”
Section: Establishment Of Cortical Polarity: the Chromatin Brings Thementioning
confidence: 99%
“…At MI stage, a similar cortical structure develops as the spindle approaches the cortex. While Ran gradient is indeed generated by chromosomes in MI in mouse oocytes [Dumont et al, 2007b], further investigation is required to test if Ran is involved in cortical polarization.…”
Section: Establishment Of Cortical Polarity: the Chromatin Brings Thementioning
confidence: 99%
“…Recently, it has been reported that the small GTPase Ran mediates chromatin signaling to control cortical polarity [5] and regulates meiotic spindle organization in mouse oocytes [6]. The evolutionarily conserved polarity proteins Par3 and Par6 are expressed in mouse oocytes and concentrate at the actin cap region, suggesting roles in establishing asymmetry in the oocytes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Le fuseau est mis en place deux heures après la rupture de l'enveloppe nucléaire et reste en place tout au long de la très longue prométaphase (qui dure six heures chez la souris), jusqu'à l'anaphase qui a lieu six à sept heures plus tard [12]. Le fuseau de la seconde division de méiose se forme rapidement à partir des microtubules qui sont restés à proximité des chromosomes après la première division de méiose, et il est stable au cours de l'arrêt CSF [13]. Les fuseaux méiotiques sont dépourvus de centrioles, ce qui exclut donc la voie centrosomique active en mitose comme mécanisme permettant de former les fuseaux en méiose.…”
Section: Revuesunclassified
“…Chez le xénope et la souris, la formation du fuseau de méiose I semble insensible à des modifications du gradient de Ran-GTP, et ce malgré l'absence de centrioles, donc en l'absence de la voie centrosomale. Il existe par conséquent un mécanisme autre que les deux voies classiques, capable de contribuer à la formation d'un fuseau de division en méiose I [11,13]. La formation du fuseau de méiose II est sensible au gradient de Ran-GTP, et le fuseau a besoin d'être stabilisé dans le temps, via les protéines MISS (MAPK-interacting and spindle-stabilizing protein) et DOC1R (Deleted in oral cancer one related) [14,15].…”
Section: Revuesunclassified